8563 One Story, Four Endings - Soumitra ranade; Rudradutt Ranade; Sonali Arun Bhatia; Archana Rao D Cruz; Mira desai; Ambika Sambasivan (Chennai : Karaditales Company Pvt. Ltd., 2018)
Raghunath boards a train from Mumbai to Vajraghat, and shares his compartment with a stranger. Raghunath$1 (Bs curiosity is piqued when the mysterious stranger starts speaking in numbers.s
One story, four Endings.